BINOL as a chiral element in mechanically interlocked molecules - Krajnc, Matthias; Niemeyer, Jochen (Beilstein Journal of Organic Chemistry, 2022)
In this minireview we present the use of the axially chiral 1,1'-binaphthyl-2,2'-diol (BINOL) unit as a stereogenic element in mechanically interlocked molecules (MIMs). We describe the synthesis and properties of such BINOL-based chiral MIMs, together with their use in further diastereoselective modifications, their application in asymmetric catalysis, and their use in stereoselective chemosensing. Given the growing importance of mechanically interlocked molecules and the key advantages of the privileged chiral BINOL backbone, we believe that this research area will continue to grow and deliver many useful applications in the future.
Keywords: axial chirality; BINOL; catenanes; interlocked molecules; rotaxanes